RUMAH BELAJAR: SARANA PENINGKATAN MOTIVASI BELAJAR SISWA - Lusiana Suciati Dewi; Sari Lestari (Bajang Institute, 2022)
To re-develop face-to-face learning motivation for students who have been studying online for a long time, the study house program is intended as a means of increasing student learning motivation. The method used in this study uses descriptive qualitative method through 4 stages, namely problem analysis, planning, implementation and evaluation. The method applied is learning by using music/songs and quizzes when study house program takes place. Participants in this study amounted to 15 people who are students from grades 3-6 SDN Nyalindung. The results showed that the study house was able to increase students' learning motivation. The study house carries out a simple and light discussion teaching and learning process. The learning house is expected to be a fun learning facility outside of school hours